STUDI PERILAKU PEMILIH (VOTER BEHAVIOUR) PADA PEMILU LEGISLATIF (Studi Kasus Dapil 2 Kabupaten Muara Enim) - Markoni Markoni (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2014)
The research is aimed to explore voter behaviour. This research is to identify  factors that influence voters in determining their choice to candidates.   It is merely case study whereas the research are mainly focus  on legislative general election at constituency 5  in Muara Enim Regency. The research area sub-districs of Semendo, Tanjung Agung and Lawang Kidul.  The main research problems to be explored are concerning with  the important factors  influence voters in determining their choice to legislator candidates. The research mainly used primary data by delivering questionaires to selected respondents. The questionaire was delivered to 660 selected respondents. It is also used secondary data to enrich the research analysis. Research finding shows  that public figures, candidate’s personal characteristic , money potitics,  ethnic,  the son of soil  are  the main  factors  effected  voters in choosing legislator candidates.